COMPREHENSIVE DIAGNOSTIC EVALUATION OF OBESITY (International Conference on Modern Science and Scientific Studies, 2025)
Obesity is one of the most widespread chronic diseases of modern society and is associated with a high risk of cardiovascular, endocrine, and metabolic disorders. Effective treatment is not possible without accurate and timely diagnosis. This article reviews current methods of obesity diagnosis, including anthropometric indicators (BMI, waist circumference, WHR), body composition assessment techniques (BIA, DEXA), as well as laboratory and differential diagnostic approaches. Special attention is given to the importance of a comprehensive and individualized diagnostic strategy that enables not only the evaluation of obesity severity but also the identification of potential secondary causes of the condition.